The Employment Effects of Working Time Reductions: Sector-Level Evidence from European Reforms - Cyprien Batut; Andrea Garnero; Alessandro Tondini (Institute of Labor Economics (IZA), 2022)
In this paper, we exploit a panel of industry-level data in European countries to study the economic impact of national reductions in usual weekly working hours between 1995 and 2007. Our identification strategy relies on the five national reforms that took place over this period and on initial differences across sectors in the share of workers exposed to the reforms. On average, the number of hours worked in more affected sectors fell, hourly wages rose, while employment did not increase. The effect on value-added per hour worked appears to be positive but non-significant.
Keywords: J20; J30; J80; 330; working time; work sharing; employment; wages; value-added